Influence of Pneumocystis jiroveci Pneumonia Prophylactic Agents on the Occurrence of Urinary Tract Infections after Renal Transplantation. (4th October 2017) - Patel, Saloni; Ott, Michael; Mergenhagen, Kari
Abstract: Background: Urinary tract infections (UTIs) are a major cause of morbidity among renal transplant recipients. This study aims to determine the influence of trimethoprim-sulfamethoxazole (TMP-SMX) vs. the composite of dapsone, atovaquone, and inhaled pentamidine intended as Pneumocystis jiiroveci pneumonia (PCP) prophylaxis on the occurrence of the composite outcome of asymptomatic bacteriuria (ASB) and UTIs post-renal transplant. Methods: A Single-center, retrospective study was conducted in recipients of renal transplant between 2013 and 2016 with a 3-month follow-up after transplantation. Patients who received TMP-SMX were compared with patients who received any second line agent for PCP prophylaxis. Significant factors were built into a multivariate logistic regression analysis with nonsignificant factors eliminated in a backwards fashion. Results: A total of 234 patients were assessed, of whom 54% received TMP-SMX and 46% received a second line agent. Baseline characteristics were similar in both groups with the exception of female gender, hypertension and previous transplant. Among the 64 patients who developed a UTI, 29 received TMP-SMX and 35 received one of the alternative agents. UTI developed on average 27.5 days post-transplant. Multivariate logistic regression analysis illustrated that TMP-SMX use was associated with reduced UTI rates vs. the composite of second line agents (Odds Ratio (OR) 1.9, 95% CI 1.0–3.5). Males were less likely than females to develop a UTI (OR 2.9, 95% CI 1.6–5.3). Conclusion: The study demonstrates that PCP prophylaxis with TMP-SMX during the initial 3 months post-renal transplant may have additional bacteriuria preventative properties. Disclosures: All authors: No reported disclosures.